Exchange Transactions of Apo Island with the Mainland From the Perspective of Wives Involved in Fish Trading - Oracion, Enrique G. (Silliman Journal, 2022)
IN COMPARISON to the position of men in the Philippine fish-eries sector, the role of women in many aspects of this trade has been widely perceived as secondary. Studies on wives' fish produc-tion activities, for instance, have shown that women's earnings is considered only as additional income to that of their husbands' (Is-rael 1991). Furthermore, in community organizations not specifically organized for women, they are merely members and are sel-dom elected or chosen as officers. Although they also attend meetings on behalf of their husbands, they do not make major decisions without prior consultation with them (Abregana 1997). Moreover, compared to their husbands' fishing activities, the wives' marketing and processing activities are deemed as only small scale. This situation underlies the pervasive perception in the country that the fishing industry is dominated by men. Women's reproduc-tive as well as domestic responsibilities have been singled out as the major factor limiting not only their participation in community, social and economic development, but their mobility and opportu-nities to engage in large scale trading activities as well (Israel 1991: 2). Abregana has pointed that these traditional role expectations attached to women have consequently deprived women of many opportunities for community involvement and other undertakings (1997). Recent studies, however, have shown that the roles wives actually play are more diverse than those of their husbands'. They combine their major tasks in homemaking with actual fishing, fish trading, and some home-based productive activities such as live-stock raising and vegetable gardening, and even acquiring a credit line (Abregana 1991, 1997;